(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
List of lichens and lichenicolous fungi of Lugans’ky Natural Reserve consists of 160 species, which belong to 71 genera, 30 families and 8 orders of Ascomycota, including 29 species new for Reserve. In Stanychno-Lugans’ke branch 70 species, in Stril’tsivs’ka steppe – 28 species, in Proval’s’ka steppe – 126 species and in Trekhizbens’ka steppe – 51 species are revealed. Ecological and substrate features as well as the distribution in branches of the Reserve are given for each taxon.